2015
DOI: 10.1039/c5cc00591d
|View full text |Cite
|
Sign up to set email alerts
|

Radical aminooxygenation of alkenes with N-fluoro-benzenesulfonimide (NFSI) and TEMPONa

Abstract: Reaction of various alkenes with commercially available N-fluorobenzenesulfonimide (NFSI) and TEMPONa provides the corresponding aminooxygenation products in moderate to good yields. Single electron transfer from readily generated TEMPONa to NFSI allows for clean generation of the corresponding bissulfonylamidyl radical along with TEMPO. N-radical addition to an alkene and subsequent TEMPO trapping provides the corresponding aminooxygenation product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 51 publications
(11 reference statements)
0
35
0
1
Order By: Relevance
“…Kinetic studies revealed rate constants from 0.13 to 11×10 7 m −1 s −1 for k add in such systems. This bifunctionalization strategy was later successfully expanded to radical alkene amidooxygenation with NFSI, to alkene azidooxygenation with the Zhdankin reagent, and to alkene aryloxygenation using either aryldiazonium salts or hypervalent iodine compounds as aryl radical precursors.…”
Section: Metal‐free Processesmentioning
confidence: 99%
“…Kinetic studies revealed rate constants from 0.13 to 11×10 7 m −1 s −1 for k add in such systems. This bifunctionalization strategy was later successfully expanded to radical alkene amidooxygenation with NFSI, to alkene azidooxygenation with the Zhdankin reagent, and to alkene aryloxygenation using either aryldiazonium salts or hypervalent iodine compounds as aryl radical precursors.…”
Section: Metal‐free Processesmentioning
confidence: 99%
“…[47][48][49][50][51][52][53] With regard to alkynes metalmediated fluorination reactions are very scarce. 51,[57][58][59][60][61][62][63][64][64][65][66][67] For instance, Muñiz and coworkers reported on alkyl-nitrogen bond formation using palladium(II) complexes and PhI(OAc) 2 as the oxidant resulting in a C(sp 3 )-N coupling via a Pd(II/IV) cycle. 54 Hammond, Xu and coworkers developed a reaction pathway to access fluorinated ketones by the reaction of alkynes with boronic acid and Selectfluor in the presence of water.…”
Section: Introductionmentioning
confidence: 99%
“…The N ‐oxyl radical is an environmentally benign and widely employed catalyst for oxidation chemistry through SET redox processes and also has high catalytic efficiency in the metal‐free cascade oxygenation–nitrogenation of cyclic olefins . In this context, by taking advantage of the SET redox cycle between TEMPO and its oxoammonium salt (TEMPO + ) counterpart, we envisaged that the bissulfonylamidyl radical and TEMPO + could be directly produced by the oxidation of NFSI with TEMPO (Scheme , step 1) and thus initiate the subsequent electrophilic addition of the N ‐radical to the alkene (Scheme , step 2) . However, owing to the high reductive tendency of TEMPO + , the corresponding carbon radical would be oxidized to the carbenium ion by TEMPO + and regenerate the TEMPO turnover cycle (Scheme , step 3).…”
Section: Methodsmentioning
confidence: 98%
“…Five‐membered N ‐oxyl 3 (PROXYL) exhibited similar efficiency (Table , entry 6). Notably, we did not observe Studer's coupling product between TEMPO and the C‐centered radical in the analysis of the 1 H NMR spectrum of the crude material of the reaction, which proved that the proposed C‐centered radical could not participate in radical coupling with TEMPO because all of the TEMPO had presumably been oxidized to TEMPO + by the excess amount of NFSI in the initial stage . This result also indicated that the catalytic turnover might be suspended in the absence of TEMPO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation